In vitro Antispasmodic and Antiinflammatory Effects of Drosera rotundifolia - Krenn, Liselotte; Beyer, Gabriele; Pertz, Heinz H.; Karall, Elisabeth; Kremser, Michaela; Galambosi, Bertalan; Melzig, Matthias F. (Arzneimittelforschung, 2004)
In investigations of the anti-inflammatory and spasmolytic effects of Drosera rotundifolia two extracts were tested in different in vitro assays. An aqueous and an ethanolic extract inhibited human neutrophil elastase, achieving IC50 values of 5 and 1 μg/mL, respectively. The very low naphthoquinone concentrations in the extracts seem not to be responsible for the effect, as the pure compounds were not effective in the test system used. Thus, flavonoids like hyperoside, quercetin and isoquercitrin, which were detected in the extracts in considerable concentrations, may contribute to the activity. These substances showed activity in the assay. Ellagic acid, detected especially in the ethanolic extract in higher amounts, was substantially less active than the flavonoids. In guinea-pig ileum the extracts led to an antispasmodic effect possibly by affecting an allosteric binding site of the muscarinic M3 receptors.
Keywords: Drosera rotundifolia, anti-in-flammatory activity, guinea-pig ileum, in vitro studies; spasmolytic activity; Flavonoids; Naphthoquinones